Knowledge of Prenatal Screening, Down Syndrome, Amniocentesis, and Related Factors among Iranian Pregnant Women: A Cross-Sectional Study - Maryam Rabiee; Zahra Jouhari; Ashraf Pirasteh (Shiraz University of Medical Sciences, 2019)
Background: The primary goal of prenatal aneuploidy screening is the early detection of pregnancies at high risk of Down syndrome (DS). The present study aimed to assess the knowledge about the prenatal screening test (PST), DS, and amniotic fluid test (AFT) among Iranian pregnant women. Methods: The present cross-sectional study was conducted from April 2013 to July 2014 in Mostafa Khomeini Educational Hospital, Tehran, Iran. The participants were recruited among pregnant women referred to the Obstetrics and Gynecology Clinic of the hospital for their routine medical evaluations. A total of 471 consecutive women fulfilling the inclusion criteria were enrolled in the study. The data collection instruments included a 9-item socio-demographic information form and a 23-item knowledge questionnaire. The latter included 9 items on DS, 10 items on PST, and 4 items on AFT. The data were analyzed using the SPSS software (version 20.0) with the Kruskal-Wallis and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: The mean score of total knowledge, PST, DS, and AFT was 9.93±4.86, 5.26±2.19, 3.25±2.42, and 1.41±1.39, respectively. There was a significant correlation between the mean score of total knowledge and the age of the mother (P=0.019), gestational age (P=0.001), educational level of the mother and spouse (P=0.001), history of birth abnormality (P=0.03), history of birth abnormality in the family (P=0.02), and sources of information (P=0.001). Conclusion: The results showed that the mean score of knowledge in pregnant women was less than half of the total scores, and total score was related to various parameters. Intervention factors that could contribute to improved knowledge and informed decision-making among pregnant women should be considered.